Sepsis and anticoagulant, is amputation a lifesaving surgery? - Neeraj Kumar; Amarjeet Kumar; Anil Kumar; Sanjeev Kumar; Veena Singh (Wolters Kluwer Medknow Publications, 2021)
Patients with severe sepsis are associated with coagulation abnormalities ranging from minimal to major activation of coagulation system, which may lead to fulminant disseminated intravascular coagulation (DIC) and multiorgan failure. Lower extremity amputation is indicated to remove ischemic, infected, or necrotic tissue or locally unresectable tumor and, at times, may be lifesaving. Peripheral artery disease and diabetes are the leading causes of non-traumatic lower extremity amputation. Amputation of lower limb in patient of severe sepsis associated with coagulation abnormalities may be limb saving surgery but may not be lifesaving surgery as in our case patient died due to multiorgan failure.